A report on the effectiveness of the “4 Crore Users Celebration Thematic Campaign TVC” of Banglalink - Sabid, Abtahi Mahbub (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.